Fisheries Production, Consumption, and Exports: Drivers of Indonesia’s Blue Economy Performance - Ni Made Cahya Chinta Kusmaputri; Diswandi Diswandi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This research aims to analyze the contribution of the fisheries sector to the implementation of the 14th Sustainable Development Goal (SDG)—namely, the performance of the blue economy in Indonesia—through economic growth. It focuses on three key variables: fisheries production, the fish consumption rate, and fisheries exports.Method: This study uses panel data regression, analyzing fisheries statistical data from 34 provinces in Indonesia with annual data spanning from 2018 to 2022. All data were processed using Eviews 10 software.Result: Using the Fixed Effect Model (FEM) approach, we found that the volume of fisheries production has a positive but insignificant effect on the performance of the blue economy in Indonesia. Meanwhile, the fish consumption rate and fisheries exports have a significant positive effect on the blue economy's performance in the country.Practical Implications for Economic Growth and Development: This research offers practical implications for the Indonesian government. Policymakers could implement measures to boost productivity in the fisheries sector, such as simplifying the investment process for investors and facilitating fisheries export activities.